Implications and Opportunities for Alumni Engagement in the Middle East and North Africa - Sublett, Lea (ICAReAlumni Conference Proceedings, 2019)
Summary The Kingdom of Saudi Arabia is a land of opportunity, but remains a mystery to most outside the Middle East and North Africa. The Kingdom’s Vision 2030 outlines a dynamic future for young, educated Saudi Arabians in new, emerging and non-oil related economies including start-ups, innovation and tech. There’s never been a more exciting time to be connected to alumni in Saudi Arabia and regionally, with the Kingdom opening up to international visitors, creating new jobs for young people educated abroad, and developing greater tolerance for digital media giving international universities regular, easy access to their alumni. Saudi Arabia is the largest economy in the Middle East and North Africa (MENA), with 50% of the Kingdom’s population of 27 million under 25 years of age. Most of these young Saudis are full-time students at universities within the Kingdom, or on government scholarships abroad. Universities internationally have benefited from Saudi Arabian government scholarships with students enrolled in programs for five or more years, resulting in an entire generation of Saudis who have returned home as global citizens and proud alumni of international alma maters. In 2017, 200,000 Saudi Arabian students were enrolled in overseas universities across North America, in the United Kingdom and Europe. Despite the large numbers of internationally educated Saudi Arabians, and the immense loyalty these alum feel to their alma maters for a transformational student and life experience, there is a reluctance from many advancement professionals to travel to the region where face-to-face interactions are essential in establishing trust and building relationships. Further, many of these institutions continue to operate a one-size-fits-all engagement program that culturally and geographically preclude participation. This paper discusses implications for advancement professionals in developing engagement strategies for alumni who live within the MENA region.